2020
DOI: 10.36469/jheor.2020.13083
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 V617F as a Marker for Long-Term Disease Progression and Mortality in Polycythemia Vera and its Role in Economic Modeling

Abstract: Background: In order to facilitate sound economic evaluations of novel treatments, health-economic models of polycythemia vera (PV) must combine effects on surrogate endpoints in trials with disease progression (DP) and mortality in long-term cohort data. Objective: We validate an economic model for PV that uses Janus Kinase 2 (JAK2) burden as a surrogate endpoint to predict DP (thrombosis, myelofibrosis, and acute leukemia) and overall survival (OS) based on progression-specific mortality. Methods: Long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Few previous reports have highlighted the impact of JAK2V617F allele burden on outcomes in PV, ET, PMF, and entire cohorts of Ph-negative MPN patients [ 7 , 9 , 10 , 11 , 31 , 33 , 34 ]. Hjelmgren et al [ 33 ] reported that PV patients with JAK2 allele burdens of >50% had inferior OS compared to those with burdens of ≤50%. In agreement with the aforementioned report, there was a trend towards inferior OS in our PV patients with high mutation loads.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous reports have highlighted the impact of JAK2V617F allele burden on outcomes in PV, ET, PMF, and entire cohorts of Ph-negative MPN patients [ 7 , 9 , 10 , 11 , 31 , 33 , 34 ]. Hjelmgren et al [ 33 ] reported that PV patients with JAK2 allele burdens of >50% had inferior OS compared to those with burdens of ≤50%. In agreement with the aforementioned report, there was a trend towards inferior OS in our PV patients with high mutation loads.…”
Section: Discussionmentioning
confidence: 99%
“…An important diagnostic criterion is the presence of JAK 2 mutation. 4 JAKs are cytoplasmic tyrosine kinases mediating signal transmission from cytokine receptors to the cell nucleus. More than 95% patients with PV express a mutation of the JAK2 (Janus kinase 2) gene, located on the short arm of chromosome 9.…”
Section: Introductionmentioning
confidence: 99%